Cerebral sinovenous thrombosis in pediatric hemolytic uremic syndrome - Kirk D. Wyatt; Vilmarie Rodriguez; Paul E. Youssef; Laurence J. Eckel; Deepti M. Warad (Research and Practice in Thrombosis and Haemostasis, 2020)
Abstract Hemolytic uremic syndrome (HUS) may result in thrombotic central nervous system complications. We present a child with diarrhea‐associated HUS who developed new‐onset focal seizures secondary to cerebral sinovenous thrombosis (CSVT). Her CSVT was treated with low‐molecular‐weight heparin. The patient’s seizures were controlled with levetiracetam, and her HUS was managed supportively with hemodialysis. Repeat imaging nearly 6 months following presentation and initiation of anticoagulation demonstrated cerebral sinus enlargement and persistent intraluminal webbing. Anticoagulation was discontinued after 6 months, and she did not experience long‐term gross neurologic sequelae. CSVT is a complication of HUS that has not been previously described. In this report, we summarize the thrombotic central nervous system complications of pediatric HUS.